2018
DOI: 10.1210/jc.2018-00972
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Management of Anti-Insulin Autoantibodies in Varying Presentations of Insulin Autoimmune Syndrome

Abstract: ContextInsulin autoimmune syndrome (IAS), spontaneous hyperinsulinemic hypoglycemia due to insulin-binding autoantibodies, may be difficult to distinguish from tumoral or other forms of hyperinsulinemic hypoglycemia, including surreptitious insulin administration. No standardized treatment regimen exists.ObjectivesTo evaluate an analytic approach to IAS and responses to different treatments.Design and SettingObservational study in the UK Severe Insulin Resistance Service.PatientsSix patients with hyperinsuline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…113,114 In case of severe hypoglycemic episodes, intravenous glucose administration may be necessary, especially in order to prevent nightly glycemic fluctuations. 88 Among the strategies aimed at reducing insulin release, somatostatin analogues, 40,115 diazoxide 41,115,116 and even pancreatectomy 18,79 have been proposed, with variable results.…”
Section: Therapymentioning
confidence: 99%
“…113,114 In case of severe hypoglycemic episodes, intravenous glucose administration may be necessary, especially in order to prevent nightly glycemic fluctuations. 88 Among the strategies aimed at reducing insulin release, somatostatin analogues, 40,115 diazoxide 41,115,116 and even pancreatectomy 18,79 have been proposed, with variable results.…”
Section: Therapymentioning
confidence: 99%
“…In addition, we found that application of sunitinib also resulted in an impairment of insulin sensitivity as determined by ITT and GTT assays and an increase in the levels of serum IAA. Therefore, we considered that sunitinib-induced hypoglycemia is associated with a decrease in glucose intake due to gastrointestinal toxicity, hyperinsulinemia and generation of IAA ( Church et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heparinized plasma samples from 7 patients with IAS were evaluated for potential interference with a C-peptide immunoassay by the UK Severe Insulin Resistance Supra-Regional Assay Service, Cambridge University Hospitals NHS Foundation Trust, Cambridge. A summary of the clinical characteristics of patients studied, the investigations undertaken on initial presentation, and the case histories have been published ( 6 , 7 ). Nonfasting blood samples were collected on ice, and plasma separated and frozen at −80 °C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperinsulinemic hypoglycemia with high C-peptide usually indicates endogenous insulin hypersecretion ( 8 ). High C-peptide immunoreactivity has been reported in IAS, even in the face of frequent profound hypoglycemia ( 6 , 7 , 9–17 ). This has the potential to confuse managing clinicians since normal endogenous C-peptide production by the pancreas is inhibited in response to exogenous insulin-induced hypoglycemia ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation